Analisis Karakteristik Pelaku Perjalanan Wisata Religi Umat Hindu Dari Pulau Bali Ke Pulau Lombok - Sideman, Ida Ayu Oka Suwati; Varapanna, Ravikan; Putra, Devian Branitasandhini (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Due to the historical journey during the sacred journey of Dang Hyang Nirarta and the expansion of the Karangasem kingdom, Bali, Lombok Island has many temples with Balinese architectural styles. This has resulted in many Hindus from Bali currently making religious trips to Lombok, so a study is needed that aims to understand the characteristics of Hindu religious tourism travelers from Bali to Lombok. This research method is qualitative research, where primary data is obtained through interview methods which are then analyzed comparatively. Of the 100 respondents, there were 55% female tourists, this figure shows a gender comparison that is close to equal. Regarding the question about the detailed purpose of religious travel, the most respondents answered was to perform yadnya (offerings), while the least detailed purpose of the trip was to perform spiritual healing or usadha (6%). A unique finding from this study is that the age group over 60 years is the second largest group as religious tourism travelers. This group is dominated by private motorcycle users with the dominant number of trip repetitions being more than two times. There is only 1 respondent from this age group who travels for the purpose of usadha, so it can be concluded that at retirement age which is also the age to carry out the vanaprasta stage of life, the health condition of religious tourism travelers is very good. Meanwhile, in the age group under 17 years old, which is the brahmacari age group, there are only 3% of religious tourism travelers who all come to participate in the piodalan, so it is highly recommended to provide education on the role of tirta yatra for the formation of the character of the young generation of Hindus in the future.